2002
DOI: 10.1080/0278682029009250
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of the Human (Child) Microclimate on Passive Aerosol Monitor Performance

Abstract: Research into the wind microclimate and its effect on the accuracy and effectiveness of passive aerosol monitors is expanding as the importance of personal monitoring versus regional monitoring increases. The important phenomena for investigation include thermal and dynamic effects of the human body, contaminant dispersion around a human body and within a building complex, and the wind environment within a building (indoor/outdoor) complex. This paper demonstrates that the microclimate around the human body pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…When the manikin was heated in quiescent indoor conditions (reference case), the CBL was able to pull the particles from the feet to the breathing zone resulting in 5.8 times higher averaged exposure compared to the case with no CBL. This result is aligned with the results of other studies (Brohus and Nielsen, ; Eisner et al., ) which showed that the CBL was able to increase inhaled concentration of pollution compared to the ambient concentration when the pollution source was located near the occupant. In case of the unheated manikin in quiescent indoor conditions (No CBL), a small portion of particles ended up in the breathing zone due to the absence of the CBL.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…When the manikin was heated in quiescent indoor conditions (reference case), the CBL was able to pull the particles from the feet to the breathing zone resulting in 5.8 times higher averaged exposure compared to the case with no CBL. This result is aligned with the results of other studies (Brohus and Nielsen, ; Eisner et al., ) which showed that the CBL was able to increase inhaled concentration of pollution compared to the ambient concentration when the pollution source was located near the occupant. In case of the unheated manikin in quiescent indoor conditions (No CBL), a small portion of particles ended up in the breathing zone due to the absence of the CBL.…”
Section: Resultssupporting
confidence: 91%
“…It has already been documented that the CBL plays an important role in pollution transport around a human body (Brohus and Nielsen, ; Eisner et al., ). Rim and Novoselac () found that in the stratified environment, the inhaled concentrations of the pollution located 0.5 m behind an occupant and 0.15 m above the floor was four times higher than the ambient concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Flow quality in the wind tunnel at low wind speeds was investigated (Eisner et al, 2002) and improved. In order to straighten the ow and decrease the turbulence levels, a ow-straightening honeycomb is used in the wind tunnel at the junction between the contraction and the test section.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research in the so-called "personal dust cloud" suggest that human activities, such as walking and running, cause the resuspension of particulate matter (PM) attached to the floor, and for as much as a 60% increase in PM concentration in the human breathing zone compared with the room background concentration (Ferro et al 2004). This is of particular concern for children and toddlers who spend a considerable amount of time close to the floor (Eisner et al 2002).…”
Section: Introductionmentioning
confidence: 99%